A comparison of extra-mucosal single layer interrupted repair vs conventional double layer repair of intestinal anastomosis: a hospital-based study - Baruah, Alfred; Choudhury, Dhirendra Nath; Patowary, Kamal Krishna (International Journal of Research in Medical Sciences, 2024)
Background: Intestinal anastomosis is a critical surgical technique used to resect and reconnect segments of the gastrointestinal tract. Traditional double-layered techniques using both absorbable and non-absorbable sutures have been widely used. However, single-layer anastomosis is gaining interest due to its simplicity, cost-effectiveness, and reduced operating time. This study aims to compare the outcomes between extra-mucosal single-layer interrupted repair and conventional double-layer repair. Methods: A prospective, randomized controlled study was conducted over six months with 42 patients undergoing intestinal resection and anastomosis. Patients were randomized into two groups: single-layer anastomosis (Group A) and double-layer anastomosis (Group B). Both groups were monitored for key outcomes such as anastomotic leak, return of bowel function, surgical site infection, and hospital stay. Results: The single-layer technique showed a significantly shorter operative time (23.8±2.5 minutes) compared to the double-layer technique (33.1±2.6 minutes). There were no statistically significant differences in anastomotic leak rates, re-interventions, or surgical site infections between the two groups. The cost of materials was lower for single-layer anastomosis. Conclusions: Single-layer anastomosis offers a time-efficient, cost-effective alternative to double-layer anastomosis with comparable clinical outcomes. The findings support the broader adoption of the single-layer technique, particularly in resource-limited settings.